2009
DOI: 10.1161/circulationaha.108.806034
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Modulators of Angina Response to Myocardial Ischemia

Abstract: Background-Although angina is often caused by atherosclerotic obstruction of the coronary arteries, patients with similar amounts of myocardial ischemia may vary widely in their symptoms. We sought to compare clinical and psychosocial characteristics associated with more frequent angina after adjusting for the amount of inducible ischemia. Methods and Results-From 2004 to 2006, 788 consecutive patients undergoing single-photon emission computed tomography stress perfusion imaging at 2 Seattle hospitals were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 46 publications
(49 reference statements)
3
30
0
3
Order By: Relevance
“…Nevertheless, despite the low ratings of depression, we found that worse angina status was associated with higher depression scores. These findings are consistent with previous studies which have reported that patients with higher depression scores (measured by CES-D) suffered more frequent angina (measured by SAQ) [5]. However, there were no associations between angina status and the Omega-3 Index.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, despite the low ratings of depression, we found that worse angina status was associated with higher depression scores. These findings are consistent with previous studies which have reported that patients with higher depression scores (measured by CES-D) suffered more frequent angina (measured by SAQ) [5]. However, there were no associations between angina status and the Omega-3 Index.…”
Section: Discussionsupporting
confidence: 92%
“…Also, as a major manifestation of coronary heart disease (CHD), angina may be one of the possible mediators in the relationship between CHD and depression. Depression can augment perceived pain [4] thus the sensation of angina may be increased in patients with depression [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with a similar burden of inducible ischemia, current anxiety and depressive symptoms are associated with more frequent angina. 73 Similar findings are present among patients who have experienced an acute coronary syndrome. 74,75 Among patients with heart failure, the prevalence of depression is even higher (eg, 30% to 35%).…”
Section: Health Status and Depressionmentioning
confidence: 52%
“…High emotional stress, loneliness, and social isolation are associated with atrial and ventricular arrhythmias [66], left ventricular dysfunction, myocardial ischemia [67], recurrent myocardial infarction [68], and increased risk of cardiac death [69], as well as other cardiac abnormalities. Likewise, personality traits such as cynical hostility [70], and emotional states such as depression [71] and anxiety [72], are linked to increased risk of CVD and worse prognosis. Lower risk, however, has been found for optimism, [73] agreeableness, 74 and other positive emotions [75].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%